2017
DOI: 10.11604/pamj.2017.28.308.12730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adverse events following immunizations surveillance system in Harare City, Zimbabwe, 2016: a descriptive cross sectional study

Abstract: IntroductionVaccines safety are monitored by looking for Adverse Events Following Immunizations (AEFIs). A review of the 2014 Harare City consolidated monthly return form (T5) revealed that 28 AEFIs were seen in 2014. However, only 21 were reported through the system. We therefore evaluated the Harare City AEFI surveillance system to assess its usefulness.MethodsA descriptive cross sectional study was conducted. Twenty one of 41 clinics were randomly selected and 51 health workers were randomly recruited. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
3
17
0
Order By: Relevance
“…Two-thirds of the facilities relied on public transport and forms were not submitted on time. These ndings are consistent with ndings by Sithole et al 2017, where the system's stability was compromised by the communication systems which led to delays in transmitting information [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two-thirds of the facilities relied on public transport and forms were not submitted on time. These ndings are consistent with ndings by Sithole et al 2017, where the system's stability was compromised by the communication systems which led to delays in transmitting information [16].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that the sensitivity of AEFISS in both districts was low. This was attributed to the passive nature of the system which relies on voluntary reporting [11,[16][17][18]. The low sensitivity might also be due to HCWs' lack of knowledge as well as inadequate community sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that perceived or real fears of being labelled as knowing too much can hinder nurses from doing the right thing in an environment where members are punished or not encouraged to stand up for their beliefs. Similar findings were reported in Zimbabwe, where nurses underreporting of immunization adverse effects were found to be due to fear of their superiors [29].…”
Section: Discussionsupporting
confidence: 85%
“…To give HCPs the confidence to report AEFIs, fears of being blamed and victimized for causing the AEFI must be allayed through sensitization workshops. According to a Zimbabwean study, key among the reasons for negative perception and low reporting of AEFI is the fear of being blamed and victimized after reporting the AEFI [45]. Results from the current study showed that about three-quarters of study participants believed that reporting an AEFI can lead to such personal consequences; such thoughts and beliefs must therefore be discarded in order to improve AEFI reporting.…”
Section: Discussionmentioning
confidence: 80%